Aesthetic Pleasure: a somaesthetic laboratory in a dance classroom - Mônica Medeiros Ribeiro (Revista Brasileira de Estudos da Presença, 2012)
This text presents a reflection on the possibility of incorporating devices potentially able to evoke sensory experiences in dance education. Based on ethnoscenological studies, on literature review and on a careful observation of Thembi Rosa’s work, Verdades Inventadas, one could regard somaesthetics and affective proprioception as important notions to think about dance. Somaesthetics seem to promote the construction of identity in dance, due to its ability to evoke pleasure in movement, connecting the individual with action.